The multifaceted impact of US trade policy on financial markets - Lukas Boer; Lukas Menkhoff; Malte Rieth (ZBW - Leibniz Information Centre for Economics, 2020)
We study the multifaceted effects and persistence of trade policy shocks on financial markets in a structural vector autoregression. The model is identified via event day heteroskedasticity. We find that restrictive US trade policy shocks affect US and international stock prices heterogeneously, but generally negatively overall, increasing market uncertainty, lowering interest rates, and leading to an appreciation of the US-Dollar. The effects are significant for several weeks or quarters. These effects reveal elements of both relative price shocks and uncertainty shocks of which the latter may be more important. Chinese trade policy shocks against the US further hurt US stocks.
Keywords: F13; F51; G10; 330; Trade policy shock; structural VAR; stock prices; exchange rates; interest rates; heteroskedasticity